Variations in the NRAMP1 gene and susceptibility to tuberculosis in West Africans. - Bellamy, R; Ruwende, C; Corrah, T; McAdam, K; Whittle, H; Hill, A (1998)
BACKGROUND: Genetic factors may affect the susceptibility to tuberculosis, but no specific genes governing susceptibility have been identified. In mice, natural resistance to infection with some mycobacteria is influenced by the gene for natural-resistance-associated macrophage protein 1 (Nramp1), but the role of the human homologue of this gene, NRAMP1, in tuberculosis is unknown. We typed polymorphisms in NRAMP1 in a case-control study of tuberculosis in the Gambia, West Africa. METHODS: Sequence-specific oligonucleotide hybridization and microsatellite analysis were used to type NRAMP1 polymorphisms in 410 adults (mean age, 34.7 years) with smear-positive pulmonary tuberculosis and 417 ethnically matched, healthy controls. Patients with human immunodeficiency virus infection were excluded. RESULTS: Four NRAMP1 polymorphisms were each significantly associated with tuberculosis. Subjects who were heterozygous for two NRAMP1 polymorphisms in intron 4 and the 3' untranslated region of the gene were particularly overrepresented among those with tuberculosis, as compared with those with the most common NRAMP1 genotype (odds ratio, 4.07; 95 percent confidence interval, 1.86 to 9.12; chi-square= 14.58; P<0.001). CONCLUSIONS: Genetic variation in NRAMP1 affects susceptibility to tuberculosis in West Africans.